2012
DOI: 10.1063/1.3701271
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of charge carrier injection on the interface energy barrier in short-channel polymeric field effect transistors

Abstract: Articles you may be interested in Organic [6,6]-phenyl-C61-butyric-acid-methyl-ester field effect transistors: Analysis of the contact properties by combined photoemission spectroscopy and electrical measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The above discussion explains two observations; increase in resistance with time and increase of rate of increase of resistance on low level dispersing, very low change of resistance with time at higher concentration of 1% graphite. This is consistent with the observations reported by Mrunal S. Mahajan et al [5] that the conductivity of PEDOT-PSS film reduces on application of high electric field.…”
Section: Discussion On the Cause Of Resistance Increase After Applicasupporting
confidence: 93%
See 1 more Smart Citation
“…The above discussion explains two observations; increase in resistance with time and increase of rate of increase of resistance on low level dispersing, very low change of resistance with time at higher concentration of 1% graphite. This is consistent with the observations reported by Mrunal S. Mahajan et al [5] that the conductivity of PEDOT-PSS film reduces on application of high electric field.…”
Section: Discussion On the Cause Of Resistance Increase After Applicasupporting
confidence: 93%
“…A metal semiconductor interface will form either a rectifying junction or an ohmic junction depending on the work functions of the semiconductor film and the contact metal [5][6][7][8]. When the interface is rectifying, the total resistance consists of two parts, the leakage resistance of a reverse biased diode and the bulk resistance of the film.…”
Section: Variation Of Resistance Of Pristine Pedot-pss Films With Timementioning
confidence: 99%
“…Examples of contacts of P3HT on Au, Co, Py, Al, and Al 2 O 3 /Co indicated a well-formed valence band in the organic material in this type of short-channel FET devices. 28 When P3HT and the contact metals are brought together an energy barrier rises, which, in the simplest case, is just due to the difference between the ionization potential and work function of the two materials. In fact, previous studies indicated that two other limiting factors must be taken into account in determining the Schottky barrier height, namely the reduction of the electronic surface dipole contribution to the metal work function by organic adsorbed molecules, 29 which modify the Fermi level in the metal close to the interface, due the interaction with the organic molecules which compress the metal surface states, and a large density of localized interface trap-states due to morphological disorder in the first layer of the organic that pins the Fermi level in the polymer.…”
Section: P3htmentioning
confidence: 99%
“…In fact, previous studies indicated that two other limiting factors must be taken into account in determining the Schottky barrier height, namely the reduction of the electronic surface dipole contribution to the metal work function by organic adsorbed molecules, 29 which modify the Fermi level in the metal close to the interface, due the interaction with the organic molecules which compress the metal surface states, and a large density of localized interface trap-states due to morphological disorder in the first layer of the organic that pins the Fermi level in the polymer. 28,30 Charge carrier injection into the organic can occur, in parallel, both over and through the interface energy barrier, via the mechanisms of thermionic emission, typically dominant at high temperatures, and tunneling, respectively. The devices can be modeled by using the equivalent circuit model of Fig.…”
Section: P3htmentioning
confidence: 99%
“…The theory of metal-induced gap states for metal/ semiconductor interfaces has been invoked to account for the charge injection at metal/polymeric or organic dielectric interfaces [7,8], despite the lack of corresponding theoretical prediction and direct experimental evidence because of their difficulties for inherently disordered dielectric materials, unlike the case of ordered inorganic semiconductors. In addition, if the metal-induced gap states also truly exist in metal/dielectric interfaces, electrons would be transferred at a very low field by a thermal assistance from occupied metal-induced gap states to localized states of the dielectric and the Schottky emission would no longer be a required process for the electron transfer.…”
Section: Introductionmentioning
confidence: 99%